Production of Sodium Silicate from Imperata cylindrica Ash by Sodium Carbonate-Assisted Alkaline Extraction - Ani Purwanti; Mukasi Wahyu Kurniawati; Anak Agung Putu Susastriawan (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2026)
The ash of Imperata cylindrica (cogon grass) contains silica that can be utilized for sodium silicate production. This work investigated its extraction using a sodium carbonate-assisted alkaline process. To evaluate silica recovery, 25 g of cogon grass ash was extracted with sodium carbonate solution at 100 ± 5 °C under different extraction times, sodium carbonate concentrations, and solvent volumes. The resulting filtrate was concentrated to obtain sodium silicate solution, and the effectiveness of the extraction process was assessed through silica recovery. The results revealed that all operating variables investigated had a significant effect on silica recovery. The best result was obtained at 75 min extraction time, 25 wt% sodium carbonate concentration, and 350 mL solvent volume, with a silica recovery of 41.59%. The increase in silica recovery was attributed to enhanced silica dissolution and improved mass transfer between the solid and liquid phases. The increase in silica recovery was influenced by more effective silica dissolution during extraction. Even though the recovery was lower than that commonly obtained from rice husk ash, cogon grass ash can still be considered a promising alternative silica source.